Mapping Research on Digital Transformation and University Image: A Scopus-Based Bibliometric Analysis - Riski Baroroh; Yus Mochamad Cholily; Dwi Priyo Utomo; Widayat Widayat; Eny Mayasari; Masdelima Azizah (AL-ISHLAH: Jurnal Pendidikan, 2026)
Digital transformation has become a strategic priority in higher education, influencing not only institutional processes but also how universities are perceived by stakeholders. However, research on digital transformation and university image remains fragmented across disciplines.This study employs a quantitative bibliometric approach to systematically map global research on digital transformation and university image. A dataset of 331 publications indexed in Scopus (2018–2025) was retrieved using a structured search strategy. Data were cleaned and analyzed using Publish or Perish for citation metrics and VOSviewer for science mapping, including co-authorship, co-occurrence, and co-citation analyses.The findings reveal a significant increase in publications after 2020, indicating growing scholarly interest in the topic. Research output is geographically concentrated in countries such as Germany, China, and the United Kingdom, with strong international collaboration networks. Keyword co-occurrence analysis identifies four major thematic clusters: digital transformation and innovation, higher education governance and strategy, digital leadership and organizational change, and stakeholder perception and university image. The results suggest a shift from technology-focused discussions toward institutional and strategic perspectives.The study highlights an emerging conceptual convergence in which digital transformation is increasingly framed as an institutional capability linked to stakeholder experience and university image formation. Despite this development, gaps remain in the operationalization and measurement of university image within digital contexts.This study provides a comprehensive overview of the intellectual structure and evolution of the field, offering directions for future research and strategic insights for higher education institutions navigating digital transformation.